2018
DOI: 10.1016/j.rasd.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between manganese and GSTP1 in relation to autism spectrum disorder while controlling for exposure to mixture of lead, mercury, arsenic, and cadmium

Abstract: Background: We previously reported a significant interactive association between polymorphisms of GSTP1 and blood manganese concentrations (BMC) with autism spectrum disorder (ASD) in Jamaican children. In this paper, we investigate the same interactive association with ASD while adjusting for the mixture of four metals (lead, mercury, cadmium, and arsenic). Method: We used data from 163 case-control pairs of children 2–8 years of age from our autism project in Jamaica, in which we collected blood for heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…The contribution of Mn for the other GSTP1 genotypes (Ile/Val and Val/Val) was not strong (i.e., <0.2) for both positive and negative models. This finding is consistent with the results from the analysis where interactive effect between Mn and GSTP1 in relation to ASD was tested without or with adjustment of other four metals in the ERAJ study (Rahbar et al., , ), which showed that higher Mn concentrations were significantly associated with ASD for only the GSTP1 Ile/Ile genotype, but this significant association was not found among children with Ile/Val or Val/Val.…”
Section: Application To the Epidemiological Research On Autism Spectrsupporting
confidence: 90%
See 3 more Smart Citations
“…The contribution of Mn for the other GSTP1 genotypes (Ile/Val and Val/Val) was not strong (i.e., <0.2) for both positive and negative models. This finding is consistent with the results from the analysis where interactive effect between Mn and GSTP1 in relation to ASD was tested without or with adjustment of other four metals in the ERAJ study (Rahbar et al., , ), which showed that higher Mn concentrations were significantly associated with ASD for only the GSTP1 Ile/Ile genotype, but this significant association was not found among children with Ile/Val or Val/Val.…”
Section: Application To the Epidemiological Research On Autism Spectrsupporting
confidence: 90%
“…So far, a significant gene‐environment interaction between GSTP1 and Mn was found when Mn was the only metal that was assessed (Rahbar et al., ). Furthermore, the model with an interaction between GSTP1 and Mn, which controls for a mixture of an additional four metals (Pb, Hg, As, and Cd) as potential confounders, has been recently conducted by investigators and suggested that the interaction effect between GSTP1 and Mn in relation to ASD was still significant after controlling for the mixture score of the other four metals (Rahbar et al., ). They conducted WQS regression to generate a weighted index of the aforementioned four metals, which was then adjusted for as a confounder in a separate conditional logistic model where the interaction between BMC and GSTP1 was assessed, since the current WQS approach (a) does not allow potential interactions of metals within a mixture, and (b) it cannot account for the clustered data in the WQS estimation process.…”
Section: Application To the Epidemiological Research On Autism Spectrmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have suggested that Mn exposure is associated with neurocognitive dysfunction and psychosis 14 . Studies have associated higher Mn blood concentration during childhood with more severe ASD symptoms 60 , lower cognitive function 50 , and inflammatory markers 61 . However, using deciduous teeth, Mn concentrations have been shown to be lower in children with the ASD during the prenatal and early postnatal periods in a twin study with higher Mn concentrations correlating with less severe ASD symptoms 11 .…”
Section: Manganese An Important Nutrient Metal With Potentially Toximentioning
confidence: 99%